Telomeric associated sequences of Drosophila recruit Polycomb-group proteins in vivo and can induce pairing-sensitive repression. - Boivin, A.; Gally, C.; Netter, S.; Anxolabehere, D.; Ronsseray, S. (Genetics, 2003)
In Drosophila, relocation of a euchromatic gene near centromeric or telomeric heterochromatin often leads to its mosaic silencing. Nevertheless, modifiers of centromeric silencing do not affect telomeric silencing, suggesting that each location requires specific factors. Previous studies suggest that a subset of Polycomb-group (PcG) proteins could be responsible for telomeric silencing. Here, we present the effect on telomeric silencing of 50 mutant alleles of the PcG genes and of their counteracting trithorax-group genes. Several combinations of two mutated PcG genes impair telomeric silencing synergistically, revealing that some of these genes are required for telomeric silencing. In situ hybridization and immunostaining experiments on polytene chromosomes revealed a strict correlation between the presence of PcG proteins and that of heterochromatic telomeric associated sequences (TASs), suggesting that TASs and PcG complexes could be associated at telomeres. Furthermore, lines harboring a transgene containing an X-linked TAS subunit and the mini-white reporter gene can exhibit pairing-sensitive repression of the white gene in an orientation-dependent manner. Finally, an additional binding site for PcG proteins was detected at the insertion site of this type of transgene. Taken together, these results demonstrate that PcG proteins bind TASs in vivo and may be major players in Drosophila telomeric position effect (TPE).